Treatment of hyponatremia in children with acute bacterial meningitis - Zheng, Feixia; Ye, Xiaoyan; Chen, Yuanyuan; Wang, Hongying; Fang, Shiyu; Shi, Xulai; Lin, Zhongdong; Lin, Zhenlang (Frontiers in Neurology, 2022)
Purpose: Few studies have evaluated hyponatremia management in children with bacterial meningitis (BM). Thus, we aimed to describe variations in clinical practice, effectiveness of sodium management, and adverse outcomes in children with BM and hyponatremia. Methods: This retrospective cross-sectional study conducted at a tertiary institution analyzed participants’ demographic, clinical, and sodium-altering treatment data. The sodium trigger for treatment was defined as pre-treatment sodium level, with response and overcorrection defined as increments of ≥5 and >10 mmol/L after 24 h, respectively. Results: This study enrolled 364 children with BM (age: <16 years; 215 boys). Hyponatremia occurred in 62.1% of patients, among whom 25.7% received sodium-altering therapies; 91.4% of those individuals had moderate/severe hyponatremia. Monotherapy was the most common initial hyponatremia treatment. After 24 h of treatment initiation, 82.4% of the patients responded. Logistic regression analyses revealed that ∆Na24 <5mmol/L (OR 15.52, 95% CI 1.71–141.06, p = 0.015) and minimum Glasgow Coma Scale (GCS) score ≤8 (OR 11.09, 95% CI 1.16–105.73, p = 0.036) predicted dysnatremia at 48h after treatment initiation. Although rare, persistent moderate/severe hyponatremia or hypernatremia at 48 h after treatment initiation was associated with a high mortality rate (57.1%). Conclusion: This study found that most cases of hyponatremia responded well to various treatments. It is important to identify and institute appropriate treatment early for moderate or severe hyponatremia or hypernatremia in children with BM. This study was limited by its non-randomized nature.